PWE-076 Impact of cirrhosis severity on survival in hepatocellular carcinoma. (8th June 2018) - Driver, Robert; Chizhande, David; Jones, Rebecca; Rowe, Ian
Abstract : Introduction: Treatment allocation and overall survival in hepatocellular carcinoma (HCC) is determined by both cancer characteristics and the severity of underlying liver disease. Treatments with the greatest chance of providing cure are often contraindicated by advanced cirrhosis. Routine healthcare data may be used to establish survival following different treatment modalities, but in the absence of biochemistry laboratory Results, few data exist to determine cirrhosis stage at HCC presentation in population-based studies. We present the Results of a pilot study to determine liver disease severity using routinely collected diagnosis and treatment codes related to cirrhosis in hospital episodes at a regional hepatobiliary cancer centre in the UK. Methods: All patients registered within three local Leeds clinical commission groups (CCGs) with a new diagnosis of HCC over a two year period (January 2013 to December 2014) were identified. Using hospital episode codes related to varices and ascites, an algorithm was developed to determine cirrhosis severity as defined by the Baveno stage. Patients were stratified according to decompensation status: compensated cirrhosis by Baveno 1 and 2 and decompensated cirrhosis by Baveno 3 and 4. This staging was validated by comparison with clinical records. Data related to demographics, liver disease aetiology and treatment allocation were collected, along with laboratory data to compare with MELD and Child Pugh (CP) scores. Kaplan-Meier survival analysis was used to compare outcomes by liver disease severity. Results: Among 78 patients with a new diagnosis of HCC (median age 69 years, 61 (78%) male), 54 patients (69%) had evidence of cirrhosis at presentation. The most frequent underlying disease aetiologies were hepatitis C (26%) and alcohol-related liver disease (24%). Patients with compensated cirrhosis had a median survival of 22.9 months and those with decompensated cirrhosis it was 2.6 months (p=0.014). The decompensated group had a median CP score of 9 and MELD of 13, compared with a median CP score of 5 and MELD of 10 in the compensated group. The Baveno algorithm correctly determined the Baveno score in 53/54 (98%) patients with cirrhosis. Conclusions: This pilot study demonstrates the successful use of an algorithm to determine Baveno stage using diagnosis and procedure codes from inpatient hospital episodes. This scoring system correlates with other validated prognostic scores in cirrhosis. In patients with HCC, the severity of the underlying liver disease must be assessed when considering outcomes for these individuals. It is expected that this algorithm will be used by the HCC-UK/National Cancer Registration and Analysis Service partnership in forthcoming population-based studies of HCC outcomes in England.